Foreigners’ Satisfaction on Services of XYZ Accounting & Audit Company - Pangwipas, Kasakorn; Junkong, Wanpen (Science, Technology, and Social Sciences Procedia, 2022)
The purposes of this research are 1) to observe the personal characteristics and information of the foreign customers which are gender, age, education level, nationality, types of business, company capital registered, duration of conducting business in Thailand, and duration of being a customer of XYZ Accounting & Audit Company, 2) to cultivate the quality of the service from foreign customers consists of 5 values which are tangibility, reliability, responsiveness, assurance, and empathy, 3) to study any factors or relationships between the quality of the service of those foreign customers of XYZ Accounting & Audit Company and the personal characteristics and information. The researchers use a questionnaire to gather information of 172 foreign persons and analyze into descriptive data with a statistical software platform which are frequencies, percentages, means, and standard deviations. Inferential data are analyzed by using Chi-Square at the level of significance 0.05. The result shows the overall service quality from foreigners’ satisfaction on services of XYZ Accounting & Audit Company are most satisfied. When they are dissected into 5 values, the value that has the most satisfaction is empathy, and the remaining values have very satisfactions orderly from the most to the least which are assurance, responsiveness, reliability, and tangibility. When the researchers test the hypothesis, the result shows that personal characteristics and information which are gender, age, education level, nationality, types of business, company capital registered, duration of conducting business in Thailand, and duration of being a customer of XYZ Accounting & Audit Company, have no significance with the service quality of XYZ Accounting & Audit Company.